Dissolvable Topical Formulations for Burst and Constant Delivery of Vitamin C - Calzado-Delgado, María del Mar; Guerrero-Pérez, María Olga; Yeung, King (American Chemical Society, 2023)
Healthy skin has a high vitamin C concentration that protects against ultraviolet (UV)-induced damage, promotes wound healing, and lowers cancer risk. The present contribution describes two drug delivery systems for topical administration of vitamin C. The electrospun poly(vinyl alcohol) (PVA) nanofiber carrier of vitamin C exhibits a burst release profile (66 mg/g/h followed by 6.3 mg/g/h). In comparison, a new composite PVA nanofiber–molecular capsule delivers vitamin C at a constant rate (8.2 mg/g/h) with a zeroth-order release profile for better therapeutic management. Both delivery systems protect vitamin C and afford increased heat stability. The molecular capsules of β-cyclodextrin with the vitamin C inclusion complex are immobilized on cellulose acetate and electrosprayed onto an electrospun PVA nanofiber mat.
Keywords: Vitamina C; Vitamin C; Nanomaterials; Electrospinning